(untitled) (Archaeologia Adriatica, 2021)
The paper presents information on the implementation of the project Cultural Landscape – a Model of Valorisation, Protection, Management and Use of Cultural Heritage - ProHeritage (UIP-2017-05-2152) in 2018 and 2019. The project is carried out in the area of the municipality of Jasenice and the town of Obrovac. It encompasses a segment of southern and southeastern Velebit and western part of Bukovica. The aim of the project is valorisation of cultural and archaeological heritage at the landscape level, in contrast to the model focused on monuments as a dominant approach in Croatia. Research area represents a test area for developing models of work for valorisation of landscape as a heritage resource.